Design of Mathematics Student Worksheet based on Discovery Learning Approach to Improving Mathematical Representation Ability Students of Grade VII Junior High School in Indonesia - Lathifah, Eka Luthfiana; man, Supar (International Journal of Engineering and Technology, 2018)
The ability of mathematical representation is very important for someone to help in solving the problem. This type of research is a development research. This article aims to obtain a student workbook design based on Discovery Learning that is oriented towards students' mathematical representation abilities. This research is a research development of Research and Development (R & D) with 4D development model which includes defining, design, development, and dissemination. This study is limited only to the design stage. Subjects in this study are students of junior high school grade VII in central java Indonesia. An instrument used in this study in the form of essay questions, questionnaire and interview guidelines. This research resulted in the worksheet (LKS) design based on Discovery Learning based on the ability of mathematical representation to improve the ability of mathematical representation. The next stage will be the research stage of development and dissemination to produce a valid, practical, and useful worksheet.